Development of the plate assay screening procedure for isolation of the mutants deficient in inactivation of peroxisomal enzymes in the yeast Yarrowia lipolytica - Nazarko, T.Y.; Mala, M. J.; Sibirny, A. A. (Біополімери і клітина, 2002)
The amine oxidase (AMO) plate assay screening procedure for isolation of the mutants deficient in inactivation of peroxisomal enzymes in the yeast Y. lipolytica has been developed. The first tagged mutants affected in the peroxisomal AMO and isocitrate lyase inactivation were generated by the insertion of a zeta-URA3 mutagenesis cassette into the genome of a zeta-free and ura3 deletion mutant strain of Y. lipolytica. Розроблено метод масового відбору мутантів дріжджів Y. lipolytica з пошкодженою інактивацією пероксисомних ферментів. Отримано перші мутанти з блоком інактивації пероксисомних амінооксидази та ізоцитратліази шляхом інсерції касети zeta-URA3 в геном вільного від zeta-елементів делеційного мутанта uraЗ Y. lipolytica. Разработан метод массового отбора мутантов дрожжей Y. lipolytica с поврежденной инактивацией пероксисомных ферментов. Получены первые мутанты с блоком инактивации пероксисомных аминооксидазы и изоцитратлиазы путем инсерции кассеты zeta-URA3 в геном свободного от zeta-елементов делеционного мутанта ura3 Y. lipolytica.